Breast self-examination practice and associated factors among women of reproductive age in southeast Ethiopia - Hussen, Abduljewad; Kumbi, Musa; Bedewi, Jemal; Lette, Abate; Nuriye, Shemsu (Frontiers in Oncology, 2023)
Regular breast self-examination is the most cost effective method for early detection of breast cancer, especially in resource limited countries. But breast self-examination practice was low among women of reproductive age. Objective: This study aims to evaluate breast self-examination practice and associated factors among women of reproductive age in southeast Ethiopia. Methods: A convergent parallel mixed-methods study design was conducted on 836 women of reproductive age. An interviewer administered questionnaire was used for the quantitative part of the study, supplemented by focus group discussions. A database was created using Epi-info version 3.5.3, and analyzed using SPSS version 20. Bivariate and multivariable logistic regressions were done to examine the effect of explanatory variables. Variables with a P value < 0.05 during multivariable logistic regressions were considered significantly associated with the dependent variable. Thematic data analysis was carried out for the qualitative study. Result: Out of eight hundred thirty-six total participants, only 20.7% had ever heard about breast self-examination practice. Also, only 13.2% of the mothers had practiced breast self-examinations. Even though the majority of the participants during the focused group discussion had knowledge about breast cancer screening, most of them stated that breast self-examination was not practiced among them. Maternal age, mothers’ level of education, and previous history of breast examination by health professionals were significant predictors of breast self-examination practices. Conclusion: This study reported a low prevalence of breast self-examination practice. Therefore, enhancing women’s education and encouraging breast examination by health professionals are essential to increasing the proportion of women performing breast self-examination.